2015
DOI: 10.3109/23744235.2015.1103895
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological factors associated with ESBL- and non ESBL-producingE. colicausing urinary tract infection in general practice

Abstract: The purpose of the study was to evaluate how use of antibiotics precedes the presence of ESBL-producing E.coli in general practice. The authors performed a triple-case-control study where three case groups were individually compared to a single control group of uninfected individuals. Urine samples were prospectively collected and retrospective statistical analyses were done. This study included 98 cases with urinary tract infection (UTI) caused by ESBL-producing E. coli, 174 with antibiotic-resistant (non-ESB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 21 publications
4
37
1
2
Order By: Relevance
“…Strains with a zone diameter for cefpodoxime of ≤24 mm (Oxoid disks) were ESBL‐screening test‐positive. ESBL‐ or AmpC production was phenotypically confirmed by the MAST test, performed as a combined‐disk method, using disks containing cefpodoxime ±ESBL and/or AmpC inhibitors (MAST®, Merseyside, UK) (Hertz et al, ).…”
Section: Commentarymentioning
confidence: 99%
“…Strains with a zone diameter for cefpodoxime of ≤24 mm (Oxoid disks) were ESBL‐screening test‐positive. ESBL‐ or AmpC production was phenotypically confirmed by the MAST test, performed as a combined‐disk method, using disks containing cefpodoxime ±ESBL and/or AmpC inhibitors (MAST®, Merseyside, UK) (Hertz et al, ).…”
Section: Commentarymentioning
confidence: 99%
“…However, we adjusted for several documented proxies for infection severity, such as prior exposure to antibiotics, comorbidities, hospitalbased diagnosis of maternal infections and prior hospital admissions. [25][26][27] We feel confident that confounding by infection severity cannot fully explain our findings, although residual confounding cannot be completely rule out.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Several risk factors have been associated with ESBL organisms causing UTIs such as recurrent UTIs, prostatic disease, recent hospital admission, travel to high prevalence countries, recent antibiotic exposure including fluoroquinolone exposure, diabetes, previous instrumentation, old age and recreational fresh water swimming . One study from Denmark that confirmed antibiotic exposure within 30 days of UTI because of ESBL‐producing organism and multiple hospital admissions are linked with community UTIs especially ESBL‐producing Escherichia coli ( E coli ) . ESBL‐producing Enterobacteriaceae are usually linked with nosocomial infection but they are also widespread in the community settings.…”
Section: Introductionmentioning
confidence: 99%